Usability Improvement based on Hierarchical Task Analysis (Case Study on i-Caring) - Muhammad Zafif Muttaqy; Angelina Prima Kurniati; Yanuar Firdaus A.W (International Journal on Information and Communication Technology (IJoICT), 2015)
i-Caring (IT Telkom i-Gracias Collaboration and e-learning) is an LMS (Learning Management System)-based e-learning integrated in i-Gracias own by IT Telkom Bandung. This application is being used to facilitate the implementation of learning activities supporting the face-to-face discussion in class. I-Caring supports some functionalities, such as instructional material storage, assignment, quizzes, and communication through chats and forum. But the great functionalities are not supported by an interactive interface, which is not comply to QUIM (Quality in Use Integrated Measurement) standard. This paper explains our research results of evaluation and recommendation process. This research is using Hierarchical Task Analysis (HTA) which has some indicators to analyze the behavior of a sample lecturers and students which are randomly selected. Based on the questionnaires answers, we analyze the relations of each points on HTA principles using SPSS Statistics 20 tools. The recommendations are then formulated to improve i-Gracias user interface quality.